KDRT dalam Prespektif Hadis - Sa'adah, Imroatus (Prodi Ilmu Hadis Fakultas Ushuluddin dan Dakwah Institut Agama Islam Negeri Madura, 2023)
Domestic violence (domestic violence) is all forms of acts of violence that occur on the basis of a comparison of genital types which cause pain or burden especially for women who are threatened with danger, pressure and separation of independence. So in this case, domestic violence, especially the abuse of a wife, is a form of chaos in society. Because there are lots of various findings in society, acts of violence not only cover wives but also spread to the scope of people's lives. The purpose of this study is to explain domestic violence in the perspective of Mawdu'i/thematic hadiths with the basis of sources from the Koran and hadith which are interrelated with religious values. Extracting data This study uses a deductive-analytical method with a deductive nature using liberary research data sources. In this case, the Koran and hadith serve as guidelines for the prohibition of hadith against forms of violence. This research produces several reasons, namely: 1) forms of violence physically, psychologically, sexually, economically. 2) explain the meaning contained therein and examples of hadiths related to forms of violence.